Preparation method of ultrahigh-flux reverse osmosis membrane
By using glycerol soaking and hot air expansion pore making, interfacial polymerization reaction and subsequent cleaning treatment in reverse osmosis membrane materials, the problem of degradation of permeability performance when increasing water flux is solved, and high throughput and High interception effect.
Patent Information
- Application Number
- CN202411670200.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-20
AI Technical Summary
When existing reverse osmosis membrane materials increase water flux, they often decrease the permeability of the membrane materials. How to economically and stably prepare high-throughput and high-interception composite reverse osmosis membranes without affecting the interfacial polymerization process is urgently needed. Technical issues.
Phase transformation curing is performed by placing the polysulfone casting film liquid and scraping it on the nonwoven surface, followed by soaking in a high concentration of glycerol solution to form a porous structure, and then adding m-phenylenediamine and homobenzene to the interfacial polymerization reaction The triformyl chloride monomer is polymerized to form a polyamide separation layer with a peak-to-grough structure, and is washed with citric acid and sodium dodecylbenzenesulfonate to ensure high throughput and high retention of the film.
A high throughput of 65.7LMH and a high desalination rate of 98.33% under high pressure conditions were achieved, which proved that this method can have both high throughput and high interception.
Smart Images

Figure CN119158423A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reverse osmosis membranes, and in particular to a method for preparing an ultra-high flux reverse osmosis membrane. Background Art
[0002] Water resources refer to natural water in various forms (such as gas, liquid or solid) in nature. Although the water resources on the earth are abundant, most of them are salt water, and fresh water resources are relatively limited. In order to solve and alleviate the problem of water shortage, the overall idea of the current solution can be summarized as "increasing revenue and reducing expenditure". Specifically, "increasing revenue" means that the total amount of available water resources needs to be increased from the source. For example, seawater and brackish water account for 97.5% of the world's total water reserves. Actively developing and utilizing seawater and inland brackish water will increase the reserves of available water resources from the source. "Reducing expenditure" means that it is necessary to consider the use of water resources, improve the utilization efficiency of water resources, and actively seek to deeply treat production and domestic wastewater through engineering and technical means to meet the standards for reuse, thereby achieving efficient reuse of water resources and achieving the goal of reducing water consumption. As an advanced wastewater treatment and seawater desalination technology, reverse osmosis technology has received continuous and widespread attention due to its efficient removal of small molecule pollutants and salt ions, and is considered to be an effective way to solve the current water shortage.
[0003] Pure water flux and salt rejection are key indicators of reverse osmosis membrane materials. However, the increase in reverse osmosis membrane water flux is usually accompanied by a decrease in the desalination performance of the membrane material. This phenomenon is called the trade-off effect between the permeability and separation performance of the membrane material. How to overcome the trade-off effect of membrane materials is an important issue currently faced in the research and development of reverse osmosis membrane materials.
[0004] Increasing the porosity of the polysulfone middle layer can increase water channels and effectively improve the water flux of the reverse osmosis membrane. The most commonly used process to increase the porosity of the middle layer is to reduce the content of polysulfone in the casting solution. However, the reduction in polysulfone content is accompanied by a loss of mechanical strength of the middle layer, which will lead to a decrease in water flux under high pressure conditions. Wang Zhi's research group at Tianjin University once introduced tannic acid into the casting solution and washed it out after the film was formed. The space originally occupied by tannic acid became a pore structure. However, due to its strong hydrophilicity, tannic acid will inevitably affect the exchange rate between the casting solution solvent and the coagulation bath solvent during the phase transition membrane formation process, resulting in a process that is difficult to control. Therefore, how to obtain a high-flux and high-retention composite reverse osmosis membrane through an economical and stable preparation process is a technical problem that people in this field urgently need to solve. Summary of the invention
[0005] In view of the above problems, the present invention provides an economical and stable preparation process, which effectively improves the porous structure of the middle layer of the composite membrane without affecting the interfacial polymerization process, ensures the integrity of the separation layer, and thus obtains a method for preparing an ultra-high flux reverse osmosis membrane with both high flux and high retention.
[0006] The technical solution of the present invention is: A method for preparing an ultra-high flux reverse osmosis membrane comprises the following steps: Step 1, preparing a polysulfone casting solution; Step 2, applying the polysulfone casting solution to the surface of the non-woven fabric by scraping, and quickly immersing it in a non-solvent coagulation bath for phase transition solidification, and then fully washing it with hot water to obtain a composite ultrafiltration membrane; Step 3, immersing the composite ultrafiltration membrane into a high concentration glycerol solution, then taking it out and heating it in a hot air oven to obtain a porous composite ultrafiltration membrane; Step 4, soaking and cleaning the porous composite ultrafiltration membrane with hot water to remove residual glycerin; Step 5, preparing an aqueous solution of m-phenylenediamine and an oily solution of trimesoyl chloride, and stirring them evenly; Step 6, coating the surface of the porous composite ultrafiltration membrane with a water phase solution of m-phenylenediamine, air purging, and an oil phase solution of trimesoyl chloride in sequence, wherein the active monomer of m-phenylenediamine and the monomer of trimesoyl chloride undergo polymerization reaction at the interface of the water-oil solution to generate a polyamide separation layer having a large number of peak-valley structures, thereby obtaining a primary composite reverse osmosis membrane; Step 7, placing the nascent composite reverse osmosis membrane into a hot air oven for heating, then taking it out and placing it into a mixed solution of citric acid and sodium dodecylbenzene sulfonate for soaking and cleaning; Step eight, prepare finished dry membrane or wet membrane according to actual needs to obtain ultra-high flux reverse osmosis membrane.
[0007] Specifically, the polysulfone casting solution includes polysulfone, polyethylene glycol 2000 and N,N-dimethylformamide, wherein the content of polysulfone is 16-19%, the content of polyethylene glycol 2000 is 5-10%, and the rest is N,N-dimethylformamide.
[0008] Specifically, the preparation sequence of the polysulfone casting solution is: first dissolving polyethylene glycol 2000 into N,N-dimethylformamide, then adding polysulfone particles for swelling, raising the temperature to 60° C. for dissolution, and the dissolution time is 12 hours.
[0009] Specifically, the non-solvent coagulation bath includes pure water or a solution mainly composed of pure water, and the solution temperature is 10-20°C.
[0010] Specifically, the high-concentration glycerol solution is a glycerol aqueous solution with a glycerol concentration of 10-20wt%.
[0011] Specifically, the m-phenylenediamine aqueous solution comprises m-phenylenediamine, an acid-binding agent, polyvinyl alcohol and pure water; Among them, the content of m-phenylenediamine is 0.5-5.0%, the acid binding agent is 0.1-2.0%, the polyvinyl alcohol is 0.1%, and the rest is pure water.
[0012] Specifically, the acid binding agent includes sodium hydroxide or triethylamine.
[0013] Specifically, the degree of polymerization of the polyvinyl alcohol is not less than 1000, and the degree of alcoholysis is not less than 98%.
[0014] Specifically, the trimesoyl chloride oil phase solution includes trimesoyl chloride and an oil phase solvent; Among them, the content of trimesoyl chloride is 0.05-0.15%, and the rest is oil phase solvent.
[0015] Specifically, the ultra-high flux reverse osmosis membrane in step eight comprises a non-woven fabric layer, a polysulfone ultrafiltration layer and a polyamide separation layer which are connected in sequence.
[0016] Beneficial effects of the present invention: The present invention performs "glycerol soaking + hot air expansion pore making + hot water cleaning" operations on the ultrafiltration membrane middle layer to improve the base membrane porosity, increase the water permeable channels of the middle layer and expand the "peak-valley structure" of the polyamide layer; polyvinyl alcohol additives are added to the aqueous phase solution of the interfacial polymerization process to improve the hydrophilicity of the polyamide separation layer on the one hand, and increase the mechanical strength of the polyamide separation layer on the other hand to prevent the collapse of the "peak-valley structure"; post-treatment cleaning adopts a combination of "citric acid + surfactant" to clean the residual amine monomers inside the polyamide on the one hand, leaving the water production channel, and remove the residual oil phase solvent on the membrane surface on the other hand, improve the membrane hydrophilicity, and improve the membrane flux. The reverse osmosis membrane obtained by the present invention is tested for performance under the conditions of 1500ppm sodium chloride solution, operating pressure of 225psi, and water temperature of 25°C, and a high flux of 65.7LMH is obtained, and a high desalination rate of 98.33% for sodium chloride is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is the process flow chart of this case; Figure 2 This is a schematic diagram of a conventional interfacial polymerization reaction membrane; Figure 3 It is a schematic diagram of the interfacial polymerization reaction of the present invention. DETAILED DESCRIPTION
[0018] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0019] The present invention can be used for manual preparation of high-flux reverse osmosis membranes in laboratories, and can also be used for large-scale production by separation membrane manufacturers. The present invention is described below with reference to FIGS. 1 and 2 ; A method for preparing an ultra-high flux reverse osmosis membrane comprises the following steps: Step 1, preparing a polysulfone casting solution and performing vacuum degassing treatment; The polysulfone casting solution comprises polysulfone, polyethylene glycol 2000 and N,N-dimethylformamide, wherein the content of polysulfone is 16-19%, the content of polyethylene glycol 2000 is 5-10%, and the rest is N,N-dimethylformamide.
[0020] The preparation sequence of the polysulfone casting solution is as follows: first dissolve polyethylene glycol 2000 in N,N-dimethylformamide, then add polysulfone particles for swelling, raise the temperature to 60°C for dissolution, and the dissolution time is 12 hours.
[0021] The vacuum degassing treatment refers to placing the above-mentioned casting liquid into a vacuum environment, while slowly rotating the stirring rod, and the vacuum degassing time is ≥12h.
[0022] Step 2: Scrape the polysulfone casting solution onto the surface of the non-woven fabric, and quickly immerse it in a non-solvent coagulation bath for phase transition solidification, and then fully wash it with hot water (the hot water temperature is 40-60° C., and the washing time is 5-10 minutes) to obtain a composite ultrafiltration membrane; Specifically, the non-woven fabric layer is made of polyester fiber, has a pore size of 100-3000nm, and a thickness of 90-120um; The thickness of the polysulfone casting liquid scraping film is controlled at 25-55um, and the separation pore size is 50-150nm; The non-solvent coagulation bath includes pure water or a solution mainly composed of pure water, and the solution temperature is 10-20°C.
[0023] The main component is a solution of pure water, such as a solution containing 1-3% N,N-dimethylformamide.
[0024] Step 3, immersing the composite ultrafiltration membrane into a high concentration glycerol solution, then taking it out and heating it in a hot air oven to obtain a porous composite ultrafiltration membrane; Specifically, the immersion time in the glycerol solution is 3-10 minutes; the oven is heated by hot air, the temperature is controlled at 70-100°C, and the heating time is 10-20 minutes; since the middle layer of the polysulfone ultrafiltration membrane and the non-woven fabric layer are made of different materials, the membrane may curl inward during the heating process, so a square frame is used for clamping during manual testing, and a roller is used to control the tension during mass production.
[0025] The high concentration glycerol solution is a glycerol aqueous solution with a glycerol concentration of 10-20wt%.
[0026] Step 4: After the porous ultrafiltration intermediate layer is prepared, it is cleaned and pore-shrinked with hot water, that is, the porous composite ultrafiltration membrane is soaked and cleaned with hot water to remove residual glycerin; Specifically, the hot water is pure water with a temperature of 50-90° C.; the cleaning operation refers to soaking the membrane in hot water for 3-5 minutes, taking it out and soaking it again with changing water, and the number of cycles is not less than 3 times to obtain a middle layer without glycerin.
[0027] Step 5, preparing an aqueous solution of m-phenylenediamine and an oily solution of trimesoyl chloride, and stirring them evenly; The m-phenylenediamine aqueous phase solution comprises m-phenylenediamine, an acid-binding agent, polyvinyl alcohol and pure water; The content of m-phenylenediamine is 0.5-5.0%, the acid-binding agent is 0.1-2.0%, the polyvinyl alcohol is 0.1%, and the rest is pure water. The acid-binding agent includes sodium hydroxide or triethylamine. The degree of polymerization of polyvinyl alcohol is not less than 1000, and the degree of alcoholysis is not less than 98%.
[0028] The trimesoyl chloride oil phase solution comprises trimesoyl chloride and an oil phase solvent; Among them, the content of trimesoyl chloride is 0.05-0.15%, and the rest is oil phase solvent.
[0029] Oil phase solvents include n-hexane, n-heptane, Isopar G and the like.
[0030] Step 6, coating the surface of the porous composite ultrafiltration membrane with a water phase solution of m-phenylenediamine, air purging, and an oil phase solution of trimesoyl chloride in sequence, wherein the active monomer of m-phenylenediamine and the monomer of trimesoyl chloride undergo polymerization reaction at the interface of the water-oil solution to generate a polyamide separation layer having a large number of peak-valley structures, thereby obtaining a primary composite reverse osmosis membrane; The flux enhancement function of the ultra-high flux reverse osmosis membrane comes from the porous structure of the polysulfone ultrafiltration layer, the large number of peak-valley structures of the separation layer, and the post-treatment cleaning process; Specifically, the aqueous solution coating refers to soaking the surface of the middle layer with the aqueous solution for 15-60 seconds. Similarly, the oil solution coating refers to coating the middle layer coated with the aqueous solution with the oil solution again for 60-180 seconds. Air purge means to use air to purge the middle layer that has been coated with the aqueous solution. The air temperature is set at 20-30℃ and the purge time is 1-10min. Air purge should ensure that there is no obvious water drop structure on the membrane surface. Step 7, placing the nascent composite reverse osmosis membrane in a hot air oven for heating, then taking it out and placing it in a mixed solution of citric acid and sodium dodecylbenzene sulfonate for soaking and cleaning, washing away the oil phase solvent and residual amine monomers on the surface of the composite membrane; Specifically, the oven temperature was set at 70-90°C and the drying time was 26 min. This operation was mainly to increase the internal cross-linking degree of the polyamide to improve the desalination rate of the composite membrane; Cleaning refers to soaking and cleaning the dried membrane in a mixed solution containing citric acid and surfactant, which is mainly used to remove the active amine monomers remaining in the membrane; In the mixed solution, the content of citric acid is 5-15%, and the content of surfactant is 0.2-1.0%; the surfactant includes sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.
[0031] Step eight, finally prepare the finished dry membrane or wet membrane according to actual needs to obtain an ultra-high flux reverse osmosis membrane.
[0032] Specifically, if a dry film is prepared, the film obtained in step seven is immersed in a 5% glycerol or triethylamine hydrochloride solution for 3 minutes, and then placed in a 70° C. oven for heating and drying for 3 minutes; if a wet film is prepared, the film obtained in step seven can be directly rolled up.
[0033] The ultra-high flux reverse osmosis membrane of this case comprises a non-woven fabric layer, a polysulfone ultrafiltration layer (middle layer) and a polyamide separation layer which are connected in sequence.
[0034] In this case, the middle layer adopts the process of "glycerol soaking + hot air expansion pore making + hot water washing" to improve the water flux of the composite membrane. Glycerol has moisturizing properties. In this case, if it is directly heated by hot air without glycerol soaking, the internal pores of the polysulfone ultrafiltration layer will collapse, and the water flux will eventually be lost. "Glycerol soaking + hot air expansion" can increase the porosity of the polysulfone ultrafiltration layer, increase the water permeable channels of the middle layer, and expand the "peak and valley structure" of the polyamide layer. The residual glycerol in the polysulfone ultrafiltration layer is washed away by hot water to prevent it from mixing into the aqueous phase solution during the interfacial polymerization process, inhibit the diffusion of the aqueous phase monomer, and then lead to a decrease in the water flux of the composite membrane. The hot water temperature range is 60-95℃. When the order of "glycerol soaking + hot air expansion" is reversed, the internal pores of the polysulfone ultrafiltration layer will collapse, resulting in the loss of water flux of the composite membrane.
[0035] The following is a specific description with examples: Embodiment 1: S1, prepare a polysulfone casting solution, including 17% polysulfone content, 8% polyethylene glycol 2000 content, and 75% N,N-dimethylformamide content (mass concentration), stir and dissolve evenly, and then put it into a vacuum oven for degassing for 12 hours; S2, use a scraper to scrape the polysulfone casting solution onto the surface of the polyester non-woven fabric, control the thickness to 45±5um, then quickly immerse it in 15℃ pure water to phase transform into a membrane, and wash it with 60℃ hot water for 10 minutes; S3, immersing the primary intermediate layer in a 20wt% glycerol aqueous solution for 5 minutes, taking it out and heating it in a 90°C oven for 15 minutes; S4, placing the porous middle layer in 70° C. hot water for 5 minutes for soaking and cleaning, and the cycle is repeated 3 times; S5, preparing an aqueous solution of m-phenylenediamine, wherein the content of m-phenylenediamine monomer is 2.0%, the content of sodium hydroxide is 0.2%, the content of polyvinyl alcohol is 0.1%, and the rest is pure water; Prepare a trimesoyl chloride oil phase solution, wherein the trimesoyl chloride content is 0.1%, and the rest is an oil phase solvent, and the oil phase solvent is Isopar G; S6, soaking the primary ecological composite membrane in the m-phenylenediamine aqueous solution for 30 seconds, taking it out and blowing it with air until there are no water droplets on the surface, and applying the trimesoyl chloride oil phase solution on the surface for 100 seconds; S7, placing the composite film in an oven at 80°C for heating for 5 minutes, and then washing it in a 10% citric acid + 0.5% sodium dodecyl sulfate solution; S8. The above membrane was placed in a sodium chloride solution with an inlet TDS of 1500ppm, an operating pressure of 225psi, and a water temperature of 25°C for performance testing. The sodium chloride retention rate was measured to be as high as 98.33±0.5%, and the flux was 65.7±5LMH.
[0036] Embodiment 2: S1, sequentially preparing the polysulfone casting solution, glycerol solution, water-oil phase solution, and citric acid + sodium dodecyl sulfate cleaning solution as described in Example 1; S2. According to the attached Figure 3 Inject each solution described in S1 into the relevant water tank; S3, turn on the oven, blowing and suction devices to reach the corresponding temperature; S4, start the equipment operation device, the non-woven fabric goes through the modules of film scraping, cleaning, glycerin soaking, glycerin drying, water-oil phase coating, drying, post-treatment cleaning, etc., and finally rolls up; S5. The above membrane was sampled and subjected to performance testing under the test conditions of an inlet TDS of 1500ppm sodium chloride solution, an operating pressure of 225psi, and a water temperature of 25°C. The sodium chloride retention rate was measured to be as high as 99.6±0.2%, and the flux was 59.8±3LMH.
[0037] Examples 1 and 2 illustrate that the method described in this case can be used for both manual testing and mass production. During the mass testing process, the performance of the obtained diaphragm is more stable due to the long-term operation of the equipment.
[0038] Comparative Example 1: S1, prepare a polysulfone casting solution, including 17% polysulfone content, 8% polyethylene glycol 2000 content, and 75% N,N-dimethylformamide content (mass concentration), stir and dissolve evenly, and then put it into a vacuum oven for degassing for 12 hours; S2, use a scraper to scrape the polysulfone casting solution onto the surface of the polyester non-woven fabric, control the thickness to 45±5um, then quickly immerse it in 15℃ pure water to phase transform into a membrane, and wash it with 60℃ hot water for 10 minutes; S3, preparing an aqueous solution of m-phenylenediamine, wherein the content of m-phenylenediamine monomer is 2.0%, the content of sodium hydroxide is 0.2%, the content of polyvinyl alcohol is 0.1%, and the rest is pure water; Prepare a trimesoyl chloride oil phase solution, wherein the trimesoyl chloride content is 0.1%, and the rest is an oil phase solvent, and the oil phase solvent is Isopar G; S4, soaking the primary ecological composite membrane in the m-phenylenediamine aqueous solution for 30 seconds, taking it out and blowing it with air until there are no water droplets on the surface, and applying the trimesoyl chloride oil phase solution on the surface for 100 seconds; S5, placing the composite film in an oven at 80°C for heating for 5 minutes, and then washing it in a 10% citric acid + 0.5% sodium dodecyl sulfate solution; S6. The above membrane was placed in a sodium chloride solution with an inlet TDS of 1500ppm, an operating pressure of 225psi, and a water temperature of 25°C for performance testing. The sodium chloride retention rate was measured to be as high as 99.18±0.3%, and the flux was 36.8±3LMH.
[0039] By comparing Example 1 with Comparative Example 1, it can be seen that without the "glycerol immersion + drying operation", the obtained membrane flux is lower, mainly because the untreated ultrafiltration intermediate layer has a lower porosity and a greater water permeation resistance. It can be seen that this case has the effect of improving the flux of the composite reverse osmosis membrane.
[0040] Comparative Example 2: S1, prepare a polysulfone casting solution, including 17% polysulfone content, 8% polyethylene glycol 2000 content, and 75% N,N-dimethylformamide content (mass concentration), stir and dissolve evenly, and then put it into a vacuum oven for degassing for 12 hours; S2, use a scraper to scrape the polysulfone casting solution onto the surface of the polyester non-woven fabric, control the thickness to 45±5um, then quickly immerse it in 15℃ pure water to phase transform into a membrane, and wash it with 60℃ hot water for 10 minutes; S3, immersing the primary intermediate layer in a 20wt% glycerol aqueous solution for 5 minutes, taking it out and heating it in a 90°C oven for 15 minutes; S4, placing the porous middle layer in 70° C. hot water for 5 minutes for soaking and cleaning, and the cycle is repeated 3 times; S5, preparing an aqueous solution of m-phenylenediamine, wherein the content of m-phenylenediamine monomer is 2.0%, the content of sodium hydroxide is 0.2%, and the rest is pure water; Prepare a trimesoyl chloride oil phase solution, wherein the trimesoyl chloride content is 0.1%, and the rest is an oil phase solvent, and the oil phase solvent is Isopar G; S6, soaking the primary ecological composite membrane in the m-phenylenediamine aqueous solution for 30 seconds, taking it out and blowing it with air until there are no water droplets on the surface, and applying the trimesoyl chloride oil phase solution on the surface for 100 seconds; S7, placing the composite film in an oven at 80°C for heating for 5 minutes, and then washing it in a 10% citric acid + 0.5% sodium dodecyl sulfate solution; S8. The above membrane was placed in a sodium chloride solution with an inlet TDS of 1500ppm, an operating pressure of 225psi, and a water temperature of 25°C for performance testing. The sodium chloride retention rate was measured to be as high as 95.92% and the flux was 18.5LMH.
[0041] By comparing Example 1 and Example 2, it can be seen that not adding polyvinyl alcohol to the aqueous phase solution will lead to a sharp decrease in the flux of the composite membrane. This may be because the surface pore size of the ultrafiltration intermediate layer is larger after the "glycerol immersion + drying" treatment, resulting in interfacial polymerization reaction in the basement membrane pore size, blocking the water production channel, or the intermediate layer obtained by interfacial polymerization collapses, resulting in a decrease in the permeation flux.
[0042] Comparative Example 3: S1, prepare a polysulfone casting solution, including 17% polysulfone content, 8% polyethylene glycol 2000 content, and 75% N,N-dimethylformamide content (mass concentration), stir and dissolve evenly, and then put it into a vacuum oven for degassing for 12 hours; S2, use a scraper to scrape the polysulfone casting solution onto the surface of the polyester non-woven fabric, control the thickness to 45±5um, then quickly immerse it in 15℃ pure water to phase transform into a membrane, and wash it with 60℃ hot water for 10 minutes; S3, immersing the primary intermediate layer in a 20wt% glycerol aqueous solution for 5 minutes, taking it out and heating it in a 90°C oven for 15 minutes; S4, placing the porous middle layer in 70° C. hot water for 5 minutes for soaking and cleaning, and the cycle is repeated 3 times; S5, preparing an aqueous solution of m-phenylenediamine, wherein the content of m-phenylenediamine monomer is 2.0%, the content of sodium hydroxide is 0.2%, the content of polyvinyl alcohol is 0.1%, and the rest is pure water; Prepare a trimesoyl chloride oil phase solution, wherein the trimesoyl chloride content is 0.1%, and the rest is an oil phase solvent, and the oil phase solvent is Isopar G; S6, soaking the primary ecological composite membrane in the m-phenylenediamine aqueous solution for 30 seconds, taking it out and blowing it with air until there are no water droplets on the surface, and applying the trimesoyl chloride oil phase solution on the surface for 100 seconds; S7, placing the composite film in an oven at 80°C and heating for 5 minutes; S8. The above membrane was placed in a sodium chloride solution with an inlet TDS of 1500ppm, an operating pressure of 225psi, and a water temperature of 25°C for performance testing. The sodium chloride retention rate was measured to be as high as 98.85±0.3%, and the flux was 44.4±5LMH.
[0043] Comparison of Example 1 and Comparative Example 3 shows that if the "citric acid + sodium dodecyl sulfate" cleaning is not performed, the flux of the membrane decreases, which is mainly due to the effects of the residual oil phase solvent on the membrane surface and the residual water phase monomer inside.
[0044] The multi-step process of the present invention prepares ultra-high flux composite reverse osmosis, has commercial feasibility, and provides an important idea for the study of composite membrane structure and mechanism.
[0045] As described above, although the present invention has been described with reference to specific preferred embodiments, it should not be construed as limiting the invention itself, and various changes in form and details may be made without departing from the spirit and scope of the invention as defined in the appended claims.
Claims
1. A method for preparing an ultra-high flux reverse osmosis membrane, characterized in that: The following steps are involved: Step 1, preparing a polysulfone casting solution; Step 2, applying the polysulfone casting solution to the surface of the non-woven fabric by scraping, and quickly immersing it in a non-solvent coagulation bath for phase transition solidification, and then fully washing it with hot water to obtain a composite ultrafiltration membrane; Step 3, immersing the composite ultrafiltration membrane into a high concentration glycerol solution, then taking it out and heating it in a hot air oven to obtain a porous composite ultrafiltration membrane; Step 4, soaking and cleaning the porous composite ultrafiltration membrane to remove residual glycerol; Step 5, preparing an aqueous solution of m-phenylenediamine and an oily solution of trimesoyl chloride, and stirring them evenly; Step 6, coating the surface of the porous composite ultrafiltration membrane with a water phase solution of m-phenylenediamine, air purging, and an oil phase solution of trimesoyl chloride in sequence, wherein the active monomer of m-phenylenediamine and the monomer of trimesoyl chloride undergo polymerization reaction at the interface of the water-oil solution to generate a polyamide separation layer having a large number of peak-valley structures, thereby obtaining a primary composite reverse osmosis membrane; Step 7, placing the nascent composite reverse osmosis membrane into a hot air oven for heating, then taking it out and placing it into a mixed solution of citric acid and sodium dodecylbenzene sulfonate for soaking and cleaning; Step eight, prepare finished dry membrane or wet membrane according to actual needs to obtain ultra-high flux reverse osmosis membrane.
2. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 1, characterized in that: The polysulfone casting solution comprises polysulfone, polyethylene glycol 2000 and N,N-dimethylformamide, wherein the content of polysulfone is 16-19%, the content of polyethylene glycol 2000 is 5-10%, and the rest is N,N-dimethylformamide.
3. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 2, characterized in that: The preparation sequence of the polysulfone casting solution is: first dissolving polyethylene glycol 2000 into N,N-dimethylformamide, then adding polysulfone particles for swelling, raising the temperature to 60° C. for dissolution, and the dissolution time is 12 hours.
4. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 1, characterized in that: The non-solvent coagulation bath comprises pure water or a solution mainly composed of pure water, and the solution temperature is 10-20°C.
5. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 1, characterized in that: The high concentration glycerol solution is a glycerol aqueous solution with a glycerol concentration of 10-20wt%; The heating temperature in the hot air oven is 50-90°C; The hot water temperature is 60-95°C.
6. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 1, characterized in that: The metaphenylenediamine aqueous phase solution comprises metaphenylenediamine, an acid binding agent, polyvinyl alcohol and pure water; Among them, the content of m-phenylenediamine is 0.5-5.0%, the acid binding agent is 0.1-2.0%, the polyvinyl alcohol is 0.1%, and the rest is pure water.
7. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 6, characterized in that: The acid binding agent includes sodium hydroxide or triethylamine.
8. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 6, characterized in that: The polymerization degree of the polyvinyl alcohol is not less than 1000, and the alcoholysis degree is not less than 98%.
9. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 1, characterized in that: The trimesoyl chloride oil phase solution comprises trimesoyl chloride and an oil phase solvent; Among them, the content of trimesoyl chloride is 0.05-0.15%, and the rest is oil phase solvent.
10. The method for preparing an ultra-high flux reverse osmosis membrane according to claim 1, characterized in that: The ultra-high flux reverse osmosis membrane in step eight comprises a non-woven fabric layer, a polysulfone ultrafiltration layer and a polyamide separation layer which are connected in sequence.
